Improved thermophysical properties of Graphene Ionanofluid as heat transfer fluids for thermal applications - Praveen Kanti; Alina Adriana Minea; K.V. Sharma; M. Revanasiddappa (Journal of Ionic Liquids, 2022)
In this study, Graphene Ionanofluid (INF) was prepared and investigated in the temperature range of 30–60 °C for stability, pH, density, specific heat, viscosity, thermal, and electrical conductivity. These new fluids are produced by dispersing the Graphene NPs in ionic liquid (IL) 1-ethyl-3-methylimidazolium chloride [EMiM]Cl in the concentration range of 0.05–0.5 wt.%. The obtained data is compared to the classical models available in the literature. The pH of the INFs lies in the range of 8.2–9.0. The results reveal that the density, electrical and thermal conductivity (TC) of INF improves with concentration. At the same time, the viscosity of INF decreases with concentration. The minimum enhancement in thermal conductivity at 30 °C is about 4.9% at a concentration of 0.05 wt.%. The most significant thermal conductivity enhancement is 27.6%, achieved at 60 °C with a concentration of 0.5% by weight. Specific heat, thermal and electrical conductivity of INF increases as temperature rises, whereas viscosity and density decrease. Furthermore, the prepared INF has a lower viscosity than the base fluid. The new correlations are formulated to determine the viscosity and thermal conductivity of INF in the studied temperature and concentration range with R2 values of 0.98 and 0.96, respectively.